General principles in free movement law: applicability and application - Snell Jukka (Edward Elgar Publishing, 2022)
The chapter investigates the relationship between the four freedoms and general principles of law. First it examines the issue of applicability. What triggers the application of general principles, and can they influence the scope of free movement law? Secondly, the chapter turns from the when question to the how question: how are the general principles applied in the Court’s free movement case law? In both parts, the analysis is directed to and a distinction is drawn between the principle of proportionality and fundamental rights. Proportionality is a principle that has been seen as inherent in free movement law and is in practice activated in almost every case. By contrast, fundamental rights have been viewed as external to free movement law and are not routinely applied, although their prevalence is growing. The overall picture that emerges is that the relationship between general principles and market freedoms is still far from settled and remains under-theorized.
Research Handbook on General Principles in EU Law: Constructing Legal Orders in Europe